Presentation of a device used by elderly women with prolapse in eastern part of Turkey - Rahman, Suheyla; Acik, Yasemin; Toraman, Zulal Asci; Celik, Aygen (Elsevier Ireland Ltd, 2006)
Objective: Presentation of a device used by three elderly women with prolapse in eastern pan of Turkey. Method: Information about device is obtained by face to face interview technique. Microbiologic examination of the device and vaginal cultures were performed. Results: Three women with genital polapse using an ancient device were found incidentally and information about device, their knowledge about genital prolapse, and solutions were obtained. Conclusion: By the help of related media and women health organizations the women especially who live in rural area should be educated about reproductive health care and if necessary health policies revisions should be considered. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: genital prolapsus; device; pessary